One Health Economics: why and how economics should take on the interdisciplinary challenges of a promising public health paradigm - Leandri, Marc; Dalmas, Laurent (Frontiers in Public Health, 2024)
In this perspective paper we argue that Economics could and should contribute to the development and implementation of the One Health approach currently emerging as a relevant interdisciplinary framework to address present and future infectious diseases. We show how proven tools from Health and Environmental Economics, such as burden evaluation, can be extended to fit the One Health multisectoral perspective. This global health framework could also benefit significantly from Economics to design efficient schemes for prevention and disease control. In return, adapting Economics to the challenges of One Health issues could pave the way for exciting developments in the Economics discipline itself, across many subfields.